OPTIMIZATION MODES OF POWER NETWORKS - Bozorov, Afzalbek Turg‘unaliyevich (Educational Research in Universal Sciences, 2023)
Nowadays in the optimization of power networks is system development of operation and optimization of branch circuits which are based on linear programming problems. One of its categories is traffic problem. The paper discusses the formulation of setting and solving problems used in the design of the most efficient power supply systems in the real sector of economy. The construction of arithmetic models of problems is carried out.